FACTORS INFLUENCING LOW BIRTH WEIGHT (LBW) AMONG MOTHER-NEONATE PAIRS AND ASSOCIATED HEALTH OUTCOMES AT COAST GENERAL HOSPITAL MOMBASA COUNTY KENYA - Jumbale, Claris Mbodze; Karanja, Professor Simon; Yusuf, Dr. Rahma Udu (Global Journal of Health Sciences, 2018)
Purpose: Low birth weight (LBW) is weight at birth of less than 2500gms regardless of the gestational age. Low birth weight is the leading cause of infants and child mortality. Most neonates / infants spend most of their weeks/ months in hospitals. Globally 20 million LBW babies are born every year throughout the world. Reports indicate that an estimated 14 % of neonates are born with LBW while the burden is estimated to be 16% in Kenya. The Objective of this study was to determine factors influencing low birth weight (LBW) and associated health outcomes associated among Mother-Neonate pairs at Coast General Hospital Mombasa County. Methods: A descriptive cross-sectional study was used to collect data on socio-demographic/socioeconomic characteristics, birth weight, and mothers' knowledge as a predictor of health outcomes among neonates. A total of 525 mothers who had delivered at Coast general hospital Mombasa County during the study period of 8months from August 2015 to March 2016 were recruited. Systematic simple random sampling was used to select study participants and a semi-structured questionnaire used to collect data. Data analysis was done by STATA 13·1 (College Station, TX, USA). Results: The prevalence of low birth weight was 29%, the prevalence was much higher than the estimated prevalence in developing countries of 16% and global prevalence; 15.5% (WHO 2012). There was significant association between low birth weight (LBW) and the following factors; caesarean section birth (adjusted relative risk (ARR) 2.33 (95% CI 1.22 - 4.44), twin birth (ARR 2.85 (95% CI 1.11 - 7.33) and previous low birth weight (ARR 2.42 (95% CI 1.04 - 5.59). Having college education level (ARR 0.41 (95% CI 0.18 - 0.92) and normal hemoglobin concentration (ARR 0.67 (95% CI 0.58 - 0.78) had protective effect on the risk of LBW. Attending ANC during pregnancy for less than 4 times as recommended by WHO was associated with ~3 fold increase in risk of LBW (CRR 2.60 (95% CI 1.69 - 4.02). The prevalence of LBW of 29% is higher than the national burden. Unique Contribution to Theory, Practice and Policy: There is need for mothers to maintain a healthy weight gain and good nutrition, start antenatal care early, make significant life style changes and pre-exciting medical condition under control to reduce the prevalence.